2007
DOI: 10.1183/09031936.00080206
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenems for the treatment of immunocompetent adult patients with nosocomial pneumonia

Abstract: The comparative effectiveness and safety of carbapenems with other b-lactams and fluoroquinolones for the empirical treatment of patients with hospital-acquired pneumonia remains controversial.In the present study, a meta-analysis of 12 relevant randomised controlled trials was performed. Overall, carbapenems were associated with lower mortality than fluoroquinolones or b-lactams, alone or in combination with aminoglycosides (odds ratio 0.72, 95% confidence interval 0.55-0.95). There was no difference between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 58 publications
3
22
0
Order By: Relevance
“…However, previous meta-analyses have reported that fluoroquinolones were associated with either more adverse outcomes compared with other antibiotics or no difference in toxicity was reported. [39][40][41][42][43] The findings of our meta-analysis about overall treatment success were similar to the results of a meta-analysis published in 2002. 44 However, only 3 of the trials included in that meta-analysis studied the effectiveness of the fluoroquinolones proposed in the 2007 guidelines.…”
Section: Discussionsupporting
confidence: 78%
“…However, previous meta-analyses have reported that fluoroquinolones were associated with either more adverse outcomes compared with other antibiotics or no difference in toxicity was reported. [39][40][41][42][43] The findings of our meta-analysis about overall treatment success were similar to the results of a meta-analysis published in 2002. 44 However, only 3 of the trials included in that meta-analysis studied the effectiveness of the fluoroquinolones proposed in the 2007 guidelines.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, early determination in the assessment of treatment success may have contributed to misclassification of outcome. 79 Second, it is evident that the observed higher mortality rate should be attributed to an open-label trial that studied the comparative effectiveness of linezolid and vancomycin for the treatment of patients with presumed or definitive gram-positive SSTIs and catheter-related bacteremia. 25 The removal of this trial from the analysis led to a result with no difference in mortality between comparators and vancomycin.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, meta-analyses are consistently used as the basis for a grade A recommendation in clinical practice guidelines, including those dealing with antimicrobial therapy [4]. Convinced by the principles of evidence-based medicine, we attempted to perform several meticulous meta-analyses in the field of antimicrobial treatment for acute bacterial exacerbations of chronic bronchitis (ABECB) [1,5], as well as for other lower respiratory tract infections [6,7].…”
Section: Statement Of Interestmentioning
confidence: 99%